Inhibition of HYBID (KIAA1199)‐mediated hyaluronan degradation and anti‐wrinkle effect of Geranium thunbergii extract. (4th November 2018) - Yoshida, Hiroyuki; Yamazaki, Kohei; Komiya, Aya; Aoki, Mika; Nakamura, Tomomi; Kasamatsu, Shinya; Murata, Takeshi; Sayo, Tetsuya; Okada, Yasunori; Takahashi, Yoshito
Abstract: Background: Hyaluronan (HA) is an essential constituent of extracellular matrix in the skin. HA reduction in the dermis and overexpression of HYBID (KIAA1199), a key molecule for HA degradation in skin fibroblasts, are implicated in facial skin wrinkling. Aims: We aimed to obtain anti‐wrinkle agent(s) by screening for inhibition of HYBID‐mediated HA degradation. Methods: Various plant extracts were screened for inhibition of HA degradation in HYBID‐stable transfectants in HEK293 (HYBID/HEK293). Inhibition of HA‐degrading activity and HYBID mRNA and protein expression by Geranium thunbergii extract was studied in skin fibroblasts and HYBID/HEK293 cells. Size distribution of newly produced HA was evaluated by preparing metabolically radiolabeled HA in skin fibroblasts. A double‐blind, randomized, and placebo‐controlled study was performed in healthy Japanese women (n = 21) by topically treating each side of the face with a lotion formulated with G. thunbergii extract or placebo for 8 weeks. Results: Among the plant extracts tested, only G. thunbergii extract abolished HA depolymerization in skin fibroblasts and HYBID/HEK293 cells by down‐regulating HYBID mRNA and protein expression and by inhibiting HYBID‐mediated HA‐degrading activity. Although untreated skin fibroblasts produced polydispersed HA, G. thunbergii extract‐treated cells produced high‐molecular‐weight HA. Treatment with G. thunbergii extract‐formulated lotion significantly improved skin elasticity and reduced skin wrinkling scores at the outer eye corner compared with the placebo formulation. Conclusions: Geranium thunbergii extract inhibited HYBID‐mediated HA degradation in vitro and showed anti‐wrinkle activity in vivo accompanying the improvement in skin elasticity. Our study provides a possible strategy for anti‐wrinkle care through inhibition of HYBID‐mediated HA degradation.